From CAR-T Cells to CAR-NK Cells: A Developing Immunotherapy Method for Hematological Malignancies - Lu, Hui; Zhao, Xiaoyan; Li, Ziying; Hu, Yu; Wang, Huafang (Frontiers in Oncology, 2021)
The approval of CD19 chimeric antigen receptor (CAR)-engineered T (CAR-T) cell products in B-cell malignancies represents a breakthrough in CAR-T cell immunotherapy. However, the remaining limitations concerning the graft-versus-host disease (GVHD) and other adverse effects (e.g., cytokine release syndromes [CRS] and neurotoxicity) still restrict their wider applications. Natural killer (NK) cells have been identified as promising candidates for CAR-based cellular immunotherapy because of their unique characteristics. No HLA-matching restriction and abundant sources make CAR-engineered NK (CAR-NK) cells potentially available to be off-the-shelf products that could be readily available for immediate clinical use. Therefore, researchers have gradually shifted their focus from CAR-T cells to CAR-NK cells in hematological malignancies. This review discusses the current status and applications of CAR-NK cells in hematological malignancies, as well as the unique advantages of CAR-NK cells compared with CAR-T cells. It also discusses challenges and prospects regarding clinical applications of CAR-NK cells.